Noninvasive monitoring of moisture uptake in Ca(NO3)2‐polluted calcareous stones by 1H‐NMR relaxometry1. (29th October 2014) - Casieri, Cinzia; Terenzi, Camilla; De Luca, Francesco; Capitani, Donatella; Proietti, Noemi
<x xml:space="preserve">Abstract</x> NMR transverse relaxation time (T2) distribution of 1H nuclei of water has been used to monitor the moisture condensation kinetics in Ca(NO3)2 · 4H2O‐polluted Lecce stone, a calcareous stone with highly regular porous structure often utilized as basic material in Baroque buildings. Polluted samples have been exposed to water vapor adsorption at controlled relative humidity to mimic environmental conditions. In presence of pollutants, the T2 distributions of water in stone exhibit a range of relaxation time values and amplitudes not observed in the unpolluted case. These characteristics could be exploited for in situ noninvasive detection of salt pollution in Lecce stone or as damage precursors in architectural buildings of cultural heritage interest. Copyright © 2014 John Wiley & Sons, Ltd.